On the Possibility of Sounding the Boundaries of the Nothern Auroral Oval by Registrations of High Frequency Signals on Superlong Radio Paths - O. V. Charkina; A. V. Zalizovski; Yu. M. Yampolski (Ukrainian Antarctic Journal, 2018)
Objective. Developing a technique for investigation of a dynamic of the equatorial boundary of the night side of the Northern auroral oval using data of registrations of scattered HF signals on superlong radio paths. Methods. Spectral, time, and time-frequency analysis of HF signals from time service stations, recorded at the Ukrainian Antarctic Akademik Vernadsky station (UAS). Selection of the spatial mode of signals scattered on the plasma inhomogeneities of the high latitude ionosphere of the northern hemisphere. The developed method is based on the measurement of the Doppler frequency shift and time of the group delay of the radio signal. Results. The possibility of studying the dynamics of the equatorial boundary of the night side of the Northern auroral oval using characteristics of scattered HF signals of time service stations registered at UAS is demonstrated. Conclusions. In the registrations of HF signals of the RWM station (55.75°N, 37.64°E) at UAS (65.25°S, 64.27°W) it is possible to select the mode scattered on the inhomogeneities of the high-latitude ionosphere of the northern hemisphere. The method for diagnosing the equatorial boundary of the auroral oval by observations on UAS of scattered radio signals from stations of the time service is proposed. It is convenient to use such stations as sources of the probe signal for diagnostic of the ionosphere so far as they have a number of advantages, including low relative frequency instability of master oscillators; weakly directed antennas and sufficiently powerful transmitters thanks to which their signals can be recorded in different regions of the globe; continuous work on a previously known schedule and, finally, the fact that they simultaneously emit at several frequencies, which expands the possibilities of their diagnostic use. The technique does not require additional transmitting devices and expensive antenna systems. The regular measurements using the suggested method allow carrying out the monitoring of auroral ionosphere, which will give the possibility for improving the existent models of its behavior.